The Social Service of the Russian Orthodox Church in the late XIX - early XX centuries in the writings of Church and Secular Researchers - Hegumen Luka (Stepanov I.) (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article covers the study’s periods of the social service of the Russian Orthodox Church from the end ofXIX century to the beginning ofXX century, the discussion about the history’s research of the social service of the Orthodox Church in the historiography of the XX century, the general levels of the social service in the same period. The author stresses that the social service of The Orthodox Church in that period got realized in unselfish and unpaid social activity.